Analysis of Spatio-temporal Characteristics of Vegetation Cover and Water Production Services in the Yellow River Basin - YAN Yifei; BAI Qiang; SUN Hu; WANG Ning; LAO Xianran (Shuitu Baochi Xuebao, 2024)
[Objective] The Yellow River Basin is an important ecological protection barrier in China, but its ecological environment is fragile. Studying the relationship between vegetation changes and water production services in the Yellow River Basin provides guarantees for its ecological construction and high-quality development. [Methods] Based on NDVI data and InVEST model, trend analysis and correlation analysis methods were used to combine vegetation change with water supply services. The temporal and spatial characteristics of NDVI and water production services in the Yellow River Basin from 2001 to 2020 were analyzed, and the trend changes and interrelationships between NDVI and water production services were studied. [Results] (1) The NDVI and water production depth of the Yellow River basin showed an increasing trend, with the growth rate of 0.05/10 a and 18.215 mm/10 a respectively. The NDVI was mainly showing a significant increase, while the water production depth was mainly showing an insignificant increase. In addition, the water production in the basin was also continuously increasing. (2) NDVI was closely related to water production depth, and there was a significant positive correlation between the two in terms of time, with a correlation coefficient of 0.75 (p<0.01). The spatial differentiation showed a positive correlation in the northeast and a negative correlation in the southwest. (3) The rate of increase in water production depth was highest under higher vegetation coverage, and NDVI was mainly positively correlated with water production depth under different vegetation coverage. However, as vegetation coverage increased, the proportion of negative correlation between NDVI and water production depth continued to increase. At present, the impact of NDVI on water production under various vegetation cover levels is positive, but as vegetation cover increases, its negative impact on water production depth will continue to increase. [Conclusion] In recent years, NDVI and water production services in the Yellow River Basin have shown a growth trend and are closely related. Currently, vegetation restoration still shows a positive effect on water production, but it should be noted that excessive vegetation restoration can have a negative impact on vegetation growth. Moderate vegetation restoration is beneficial for water production services in the Yellow River Basin.